Photocatalytic Oxidation Kinetics for Desulfurization of Dibenzothiophene with Al2O3/g-C3N4 Heterojunction (International Journal of Petroleum Technology, 2015)
Al2O3/g-C3N4 heterojunction is fabricated for the photocatalytic removal of dibenzothiophene in oil-water biphasic system and the reaction kinetics is studied. The influences of Al2O3/g-C3N4 ratio and photocatalyst dosage on reaction rate constant are investigated. The results indicate that the optimum addition of Al2O3/g-C3N4 composite is 0.075 g in 100 mL reaction system and the photooxidation kinetics of dibenzothiophene follows first-order reaction. The sulfur removal of dibenzothiophene can reach 90.3 % in 4 h under the irradiation of mercury lamp and the sulfur content can be decreased from 200 to below 20 ppm.
Keywords: Desulfurization; Dibenzothiophene; Al2O3/g-C3N4; Photocatalytic oxidation; Kinetics.